Cultivating Retention: Investigating the Mediating Role of Organizational Culture in the Relationship between Job Satisfaction, Work Environment, and Turnover Intentions - Djoko Soelistya; Rahmat Agus Santoso; Diah syarif (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study was conducted to determine and analyze things that affect the occurrence of turnover intention in contractor companies in Manyar Gresik. The study also aims to prove the effect of job satisfaction and work environment on turnover turnover through organizational culture as mediation. The type of research used is quantitative research where the population and sample in this study are employees of project contractors in Manyar Gresik totaling 271 respondents. Data analysis techniques were used to provide answers from respondents through questionnaires and data management in this study using the SmartPLS 3.0 Software program. The results of this study show that the effect directly shows that (1) job satisfaction does not have a significant effect on turnover intention; (2) job satisfaction has a significant effect on organizational culture; (3) the work environment has a significant effect on organizational culture; (4) the work environment has a significant effect on turnover intention, (5) and the culture of organization has a significant effect on turnover intention, while the indirect influence shows that (6) job satisfaction on turnover has a less significant effect without going through an organizational culture that can work as full mediation; (7) and the work environment on turnover has a significant influence even through organizational culture that can work as a partial mediation. Therefore, attention and consistency in the implementation of policies and rules that have been cultured must be maintained properly to foster employee trust in the company so that they no longer think about leaving the company.